PROFIL KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DALAM MENYELESAIKAN PERMASALAHAN SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DITINJAU BERDASARKAN KEMAMPUAN MATEMATIKA DASAR - Oktapiyanti Oktapiyanti; Deajeng Putri Salamah; Anna Refa Zhavira Sundamanik; Wahyu Hidayat; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The author conducts research in class VIII of Cisarua 1 Junior High School using a qualitative description research method that is a case study by reviewing the learning style and basic abilities of students in understanding mathematics subjects through solving TVLES problems (Two Variable Linear Equation System). So that from this obtained a description of the mathematical connection capabilities of these students. This study uses a mathematical connection ability test instrument and interview guidelines. The sample from this study were 36 sixth grade students of Cisarua 1 Junior High School. The results of the data show the percentage score of each indicator based on the basic ability obtained by students' mathematical connection skills in solving system problems of two variable linear equations, namely the upper group with an average of 68.5%, the middle group with an average of 63%, and the lower group evenly - average 47.75%.